7T for clinical imaging of benign peripheral nerve tumors: preliminary results - Amrami, Kimberly K; Chebrolu, Venkata V; Felmlee, Joel P; Frick, Matthew A; Powell, Garret M; Marek, Tomas; Howe, Benjamin M; Fagan, Andrew J; Kollasch, Peter D; Spinner, Robert J (Acta neurochirurgica, 2023)
PURPOSE: MRI has become an essential diagnostic imaging modality for peripheral nerve pathology. Early MR imaging for peripheral nerve depended on inferred nerve involvement by visualizing downstream effects such as denervation muscular atrophy; improvements in MRI technology have made possible direct visualization of the nerves. In this paper, we share our early clinical experience with 7T for benign neurogenic tumors. MATERIALS: Patients with benign neurogenic tumors and 7T MRI examinations available were reviewed. Cases of individual benign peripheral nerve tumors were included to demonstrate 7T MRI imaging characteristics. All exams were performed on a 7T MRI MAGNETOM Terra using a 28-channel receive, single-channel transmit knee coil. RESULTS: Five cases of four pathologies were selected from 38 patients to depict characteristic imaging features in different benign nerve tumors and lesions using 7T MRI. CONCLUSION: The primary advantage of 7T over 3T is an increase in signal-to-noise ratio which allows higher in plane resolution so that the smallest neural structures can be seen and characterized. This improvement in MR imaging provides the opportunity for more accurate diagnosis and surgical planning in selected cases. As this technology continues to evolve for clinical purposes, we anticipate increasing applications and improved patient care using 7T MRI for the diagnosis of peripheral nerve masses.
Keywords: magnetická rezonanční tomografie; Peripheral Nervous System Neoplasms; nádory periferního nervového systému; Neoplasms; 7T; Magnetic Resonance Imaging; Benign; Humans; Peripheral Nerves; Nerve tumor; Signal-To-Noise Ratio; periferní nervy; nádory; poměr signál - šum; Nerve imaging; lidé